Bank Responsibility to Customers Due to Unauthorized Actions by Debt Collectors in Resolving Bad Credit Cards - I Gusti Ayu Widiadnyani; Muhammad Panji Mahardika; Lily Marheni; Nyoman Sukayasa (Universitas Wiralodra, 2026)
Credit cards offer significant convenience in making payments. However, many customers in Indonesia are currently delinquent on their credit card payments. Bank Indonesia regulations permit the use of debt collection services, but they must be legally accountable if a debt collector commits an unlawful act. This research addresses two main issues: the legal relationship between banks and debt collectors in resolving bad credit card debts and the bank's liability for the debt collector's unlawful actions in resolving bad credit cards. This study employed normative research as its research methodology. This seeks to determine the truth about the bank's obligation to consumers for the illegal acts of debt collectors in settling faulty credit cards, based on the normative side of legal logic. In order to resolve bad credit cards, banks and debt collectors have a legal connection based on a power of attorney agreement. Additionally, the bank is liable for the illegal activities carried out by the debt collector in order to resolve faulty credit cards. This is because the bank and the debt collector have a legal relationship.